Degenerate CD8 Epitopes Mapping to Structurally Constrained Regions of the Spike Protein: A T Cell-Based Way-Out From the SARS-CoV-2 Variants Storm - Boni, Carolina; Cavazzini, Davide; Bolchi, Angelo; Rossi, Marzia; Vecchi, Andrea; Tiezzi, Camilla; Barili, Valeria; Fisicaro, Paola; Ferrari, Carlo; Ottonello, Simone (Frontiers in Immunology, 2021)
There is an urgent need for new generation anti-SARS-Cov-2 vaccines in order to increase the efficacy of vaccination and its broadness of protection against viral variants that are continuously arising and spreading. The effect of variants on protective immunity afforded by vaccination has been mostly analyzed with regard to B cell responses. This analysis revealed variable levels of cross-neutralization capacity for presently available SARS-Cov-2 vaccines. Despite the dampened immune responses documented for some SARS-Cov-2 mutations, available vaccines appear to maintain an overall satisfactory protective activity against most variants of concern (VoC). This may be attributed, at least in part, to cell-mediated immunity. Indeed, the widely multi-specific nature of CD8 T cell responses should allow to avoid VoC-mediated viral escape, because mutational inactivation of a given CD8 T cell epitope is expected to be compensated by the persistent responses directed against unchanged co-existing CD8 epitopes. This is particularly relevant because some immunodominant CD8 T cell epitopes are located within highly conserved SARS-Cov-2 regions that cannot mutate without impairing SARS-Cov-2 functionality. Importantly, some of these conserved epitopes are degenerate, meaning that they are able to associate with different HLA class I molecules and to be simultaneously presented to CD8 T cell populations of different HLA restriction. Based on these concepts, vaccination strategies aimed at potentiating the stimulatory effect on SARS-Cov-2-specific CD8 T cells should greatly enhance the efficacy of immunization against SARS-Cov-2 variants. Our review recollects, discusses and puts into a translational perspective all available experimental data supporting these “hot” concepts, with special emphasis on the structural constraints that limit SARS-CoV-2 S-protein evolution and on potentially invariant and degenerate CD8 epitopes that lend themselves as excellent candidates for the rational development of next-generation, CD8 T-cell response-reinforced, COVID-19 vaccines.